An Innovative Bio-Vehicle for Resveratrol and Tocopherol Based on Quinoa 11S Globulin—Nanocomplex Design and Characterization - Alejandra J. Rubinstein; Guadalupe Garcia Liñares; Valeria Boeris; Oscar E. Pérez (Pharmaceutics)
Nanocomplexes, which possess immense potential to function as nanovehicles, can link diverse ligand compounds. The objective of the present study was to design and characterize resveratrol (RSV)- and tocopherol (TOC)-loaded 11S quinoa seed protein nanocomplexes. Firstly, molecular docking was performed to describe the probable binding sites between protein and ligands, and binding energies of −5.6 and −6.2 kcal/mol were found for RSV and TOC, respectively. Isothermal titration calorimetry allowed us to obtain the thermodynamic parameters that described the molecular interactions between RSV or TOC with the protein, finding the complexation process to be exothermic and spontaneous. 11S globulin intrinsic fluorescence spectra showed quenching effects exerted by RSV and TOC, demonstrating protein–bioactive compound interactions. The application of Stern–Volmer, Scatchard, and Förster resonance energy transfer models confirmed static quenching and allowed us to obtain parameters that described the 11S-RSV and 11S-TOC complexation processes. RSV has a higher tendency to bind 11S globulin according to ITC and fluorescence analysis. Secondly, the protein aggregation induced by bioactive compound interactions was confirmed by dynamic light scattering and atomic force microscopy, with diameters <150 nm detected by both techniques. Finally, it was found that the antioxidant capacity of a single 11S globulin did not decrease; meanwhile, it was additive for 11S-RSV. These nanocomplexes could constitute a real platform for the design of nutraceutical products.